2013
DOI: 10.1002/emmm.201202046
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of master autophagy regulator TFEB results in clearance of toxic protein and correction of hepatic disease in alpha‐1‐anti‐trypsin deficiency

Abstract: Alpha-1-anti-trypsin deficiency is the most common genetic cause of liver disease in children and liver transplantation is currently the only available treatment. Enhancement of liver autophagy increases degradation of mutant, hepatotoxic alpha-1-anti-trypsin (ATZ). We investigated the therapeutic potential of liver-directed gene transfer of transcription factor EB (TFEB), a master gene that regulates lysosomal function and autophagy, in PiZ transgenic mice, recapitulating the human hepatic disease. Hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 67 publications
2
112
0
2
Order By: Relevance
“…TFEB overexpression has also shown therapeutic effects in mouse models of α1-antitrypsin deficiency, the most common genetic cause of liver disease (Pastore et al, 2013). In this case as well, enhanced intracellular clearance represents the major therapeutic mechanism, as induction of autophagy by TFEB reduces the levels of α1-antitrypsin accumulation and ameliorates liver injury.…”
Section: Tfeb As a Therapeutic Target For Diseasesmentioning
confidence: 99%
“…TFEB overexpression has also shown therapeutic effects in mouse models of α1-antitrypsin deficiency, the most common genetic cause of liver disease (Pastore et al, 2013). In this case as well, enhanced intracellular clearance represents the major therapeutic mechanism, as induction of autophagy by TFEB reduces the levels of α1-antitrypsin accumulation and ameliorates liver injury.…”
Section: Tfeb As a Therapeutic Target For Diseasesmentioning
confidence: 99%
“…For instance, overexpression of TFEB rescues toxicity of α-synuclein and protects dopaminergic neurons in a rat model of Parkinson's disease that is induced by viral overexpression of α-synuclein (Decressac et al, 2013); it also ameliorates toxicity by enhancing the clearance of misfolded polyglutamine-expanded ( polyQ) huntingtin protein (Tsunemi et al, 2012) and the mutant androgen receptor that causes X-linked spinal and bulbar muscular atrophy (Cortes et al, 2014). Gene transfer of TFEB alleviates pathology in a mouse model of alpha-1-anti-trypsin deficiency (Pastore et al, 2013). Moreover, activation of autophagy and lysosomal activity by TFEB attenuates the pathological phenotype in mouse models of Pompe disease (Spampanato et al, 2013).…”
Section: Tfeb and Zkscan3 -The Master Autophagy Regulatorsmentioning
confidence: 99%
“…9 The problem of applying gene therapy to treat diseases associated with protein misfolding and aggregation has now been addressed, in part, by a study concerning liver disease. 10 Andrea Ballabio and colleagues previously described the coordinated lysosomal expression and regulation (CLEAR) network, 11 which is controlled through the transcription factor TFEB, and demonstrated that it regulates macroautophagy in an MTOR-dependent manner. [12][13][14] The possibility of manipulating TFEB to treat a disease by upregulating macroautophagy was seen with the finding that overexpression of TFEB, or its upstream regulator PPARGC1A/ PGC-1α, rescues the neurodegenerative effects resulting from HTT toxicity.…”
mentioning
confidence: 99%
“…15 Now, a paper from Nicola BrunettiPierri and colleagues has advanced this knowledge by using TFEB-based gene therapy to treat a mouse model of α 1 -antitrypsin deficiency. 10 In this disease, a mutant form of SERPINA1/A1AT accumulates in particular in liver cells, the site of its synthesis, and can lead to cirrhosis. In addition, a deficiency of SERPIN1A in the lungs can lead to emphysema.…”
mentioning
confidence: 99%
See 1 more Smart Citation